Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Cooperative Learning Tipe Talking Stick di Kelas V Sekolah Dasar - Putri, Fanny Amelia; Suherman, Farida (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This study is driven by the fact that education is still mostly a teacher's responsibility and that teachers rarely employ engaging and creative teaching strategies to get students more involved, including playing games. This study seeks to explain how the talking sticks cooperative learning approach improves learning results. Classroom action research (PTK), which combines qualitative and quantitative methods, falls under this category. 26 pupils from class V SD Negeri 05 Padang Pasir Padang served as the study's participants. The study's results demonstrate that cycle I's assessment of lesson plans yielded an average score of 83% (B), and cycle II's score increased to 94.44% (SB). The average level of teacher involvement was 82.50% (B) in cycle I, and it increased to 95.00% (SB) in cycle II. Student activities, meanwhile, had an average value of 82.50% (B) in cycle I and grew to 95.00% (SB) in cycle II. In light on account of this, it may be claimed that the cooperative learning model using talking sticks enhance the fifth-grade students' integrated theme learning process at SD Negeri 05 Padang Pasir, Padang City.